Safety and efficacy of inpatient pulmonary rehabilitation for patients hospitalised with an acute exacerbation of chronic obstructive pulmonary disease: a systematic review protocol. Issue 6 (23rd June 2021) - Zhu, Kai; Gill, Jagdeep; Kirkham, Ashley; Chen, Joel; Ellis, Amy; Crosbie, Stephanie; Denson-Camp, Holly; Peters, Hannah; Camp, Pat
Abstract : Introduction: Pulmonary rehabilitation (PR) following an acute exacerbation of chronic obstructive pulmonary disease (AECOPD) reduces the risk of hospital admissions, and improves physical function and health-related quality of life. However, the safety and efficacy of in-hospital PR during the most acute phase of an AECOPD is not well established. This paper describes the protocol for a systematic review with meta-analysis to determine the safety and efficacy of inpatient acute care PR during the hospitalisation phase. Methods and analysis: Medical literature databases and registries MEDLINE, EMBASE, Physiotherapy Evidence Database, Cumulative Index to Nursing and Allied Health Literature, Canadian Agency for Drugs and Technologies in Health, CENTRAL, Allied and Complementary Medicine Database, WHO trials portal and ClinicalTrials.gov will be searched for articles from inception to June 2021 using a prespecified search strategy. We will identify randomised controlled trials that have a comparison of in-hospital PR with usual care. PR programmes had to commence during the hospitalisation and include a minimum of two sessions. Title and abstract followed by full-text screening will be conducted independently by two reviewers. A meta-analysis will be performed if there is sufficient homogeneity across selected studies or groups of studies. The Population, Intervention, Comparator, Outcomes and Study characteristics framework will be used to standardise the data collection process. The quality of the cumulative evidence will be assessed using the Grading of Recommendations, Assessment, Development and Evaluations framework. Ethics and dissemination: AECOPD results in physical limitations which are amenable to PR. This review will assess the safety and efficacy of in-hospital PR for AECOPD. The results will be presented in a peer-reviewed publication and at research conferences. Ethical review is not required for this study. PROSPERO registration number: CRD42021198877.